User Resistance in Information System Implementation: A Review of Related Literature - Dalisay, Ferdinand V. (Asian Journal of Multidisciplinary Studies, 2019)
The identified salient reason for most of Information System (IS) implementation to fail is user resistance. User resistance has long been acknowledged as a critical issue during the implementation of an Information System (IS). Many research papers have discussed the reasons for user resistance; however, few papers review the implementers’ responses. This paper reviews the reasons why users resist in the implementation of an Information System. In addition, this paper will also discuss different responses of the information system implementers when there is user resistance.